Chondroprotective and anti‐inflammatory effects of amurensin H by regulating TLR4/Syk/NF‐κB signals. Issue 2 (25th December 2019) - Ma, Pei; Yue, Lifeng; Yang, Hui; Fan, Yannan; Bai, Jinye; Li, Shuyi; Yuan, Jiqiao; Zhang, Ziqian; Yao, Chunsuo; Lin, Mingbao; Hou, Qi
Abstract: The low‐grade, chronic inflammation initiated by TLR4‐triggered innate immune responses has a central role on early osteoarthritis. Amurensin H is a resveratrol dimer with anti‐inflammatory and anti‐apoptotic effects, while its effects on TLR‐4 signals to inhibit osteoarthritis are still unclear. In the present study, treatment with amurensin H for 2 weeks in monosodium iodoacetate‐induced mice significantly slows down cartilage degeneration and inflammation using macroscopic evaluation, haematoxylin and eosin (HE) staining and micro‐magnetic resonance imaging. In IL‐1β‐stimulated rat chondrocytes, amurensin H suppresses the production of inflammatory mediators including nitric oxide, IL‐6, IL‐17, PGE2 and TNF‐α using Greiss and ELISA assay. Amurensin H inhibits matrix degradation via decreasing levels of MMP‐9 and MMP‐13 using Western blot assay, promotes synthesis of type II collagen and glycosaminoglycan using immunostaining and safranin O staining, respectively. Amurensin H inhibits intracellular and mitochondrial reactive oxygen species (ROS) generation, and mitochondrial membrane depolarization using DCFH‐DA, MitoSOX Red and JC‐1 assay as well. IL‐1β stimulates TLR4 activation and Syk phosphorylation in chondrocytes, while amurensin H inhibits TLR4/Syk signals and downstream p65 phosphorylation and translocation in a time and dose‐dependent manner. Together, these results suggest that amurensin H exerts chondroprotective effects by attenuating oxidative stress, inflammation and matrix degradation via the TLR4/Syk/NF‐κB pathway.